Quranic Notion Of Human Presence On Toshihiku Izutsu Perspective - Rezki Kaulan Maisurah; Alhafidh Nasution; Amelia Japana (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
Human presence is closely related to the role of God as a creator. People have the natural nature of not denying the existence of God, and people desperately need the existence of God to have a handle in life so that what they do becomes more meaningful and gives hope for a happy ending. Furthermore, the destiny of man in the Qur'an is that Allah has given a particular degree or measure or limit in the person, nature, or maximum ability of His being. The position of destiny in human life is not determined in eternal times but along with the ongoing process. This article was written using the method of documentation study in the analysis of the concept between God and man on Toshihiko Izutsu perspective. As a result, Izutsu described the four relationships between God and Man. Firstly, The Ontological Relationship which discussed a relation between God and man, that God as creator and man as a human being. Following the first, there are a Communicative Relationship between God and man which brought into close correlation through mutual communication. So comes the third, was Master-servant relationship, that God as Master (Rabb), and man as a servant (abd). And the final was Ethical Relationship, which discussed an Ethic doing on a man obligation on his God, nor God's commandments or prohibitions and how God will on His creatures. Keberadaan manusia berkaitan erat dengan peran Tuhan sebagai Sang Khalik. Adalah sifat alamiah seorang manusia untuk tidak menyangkal keberadaan Tuhan, dan sangat membutuhkan keberadaanNya sebagai Penunjuk dalam kehidupan, agar apa yang mereka lakukan menjadi lebih bermakna dengan harapan dapat menjadi akhir yang bahagia. Akhir yang bahagia memang merupakan tujuan setiap manusia, namun takdir bisa berbeda. Takdir manusia, dalam al-Qur'an, disebutkan bahwa Allah telah memberikan derajat, ukuran, dan batasan tertentu dalam diri seseorang ataupun batas kemampuannya sesuai kehendakNya. Takdir manusia tidak menentu dan dapat berjalan seiring dengan proses yang sedang berlangsung. Artikel ini ditulis menggunakan metode kualitatif dengan menggunakan pendekatan literatur untuk menganalisa konsep antara Tuhan dan manusia menurut Toshihiko Izutsu. Dari penelitian tersebut penulis menemukan bahwa adanya pemaparan Izutsu terkait empat hubungan antara Tuhan dan Manusia. Pertama yaitu Hubungan Ontologis antara Tuhan dan manusia, dimana Tuhan sebagai pencipta dan manusia sebagai makhluk ciptaan. Kedua, Hubungan Komunikatif antara Tuhan dan manusia yaitu adanya korelasi yang erat melalui komunikasi timbal balik. Ketiga, Hubungan Tuan-pelayan, dimana Tuhan sebagai Tuan (Rabb), dan manusia sebagai pelayan (hamba). Dan terakhir, Hubungan Etis yaitu etika yang berkaitan dengan perintah dan larangan Tuhan dan bagaimana Tuhan menghendaki ciptaan-Nya.